Extraction of rose hydrosol from Yunnan Dark Red Rose by steam distillation: optimization, antioxidant activity, and flavor assessment - Wan, Yilai; Xu, Chengjian; Zhu, Zhongyan; Liu, Wenyu; Wei, Changqing; Yi, Yuwen; Liu, Zhanxia; Wang, Ting; Zhu, Nan; Xiao, Hang (Frontiers in Sustainable Food Systems, 2024)
The rose hydrosol was extracted from Yunnan Dark Red Rose petals by steam distillation, and the extraction process was optimized by response surface methodology. Besides, volatile compounds in the rose hydrosol were analyzed by headspace solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) and its antioxidant activity was also verified. The results showed that the sensory score of rose hydrosol was the highest when the ratio of flower to liquid was 1:2 (w/v), the reflux time was 5 min, the distillation temperature was 120 ℃, and the concentration of sodium chloride was 3%. The scavenging rates of rose hydrosol on DPPH, ·OH and superoxide anion (·O2-) were 26.13%, 55.56% and 10.76% respectively, the polyphenol content was 14.9 ± 2.5 GAE mg/g, and the content of flavonoids in pure dew was 19.3 ± 1.3 RE mg/g which indicated that the extracted rose hydrosol had adequate antioxidant activity. Our study provides a theoretical reference for the utilization of rose hydrosol in food and cosmetic fields.